Pharmaceutical Camel Products; Marketing Strategies for Successful International Penetration - Aliedan, Meqbel; Alyahya, Mansour; Dhruvakumar, Sneha; Sreeharsha, Nagaraja; Fattepur, Santosh (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: This research aimed at how Saudi Arabia can be the global giant producer of pharmaceutical camel products using strategies for successful international penetration. In certain areas of Asia and Africa camel milk, urine, skin, and intestines are used as medicine from ancient days. Camel milk is the source of Vitamin C, B1, and B2. Heparin and gelatin are also extracted from the intestine and skin of the camel, respectively. While it is widely acknowledged that pharmaceutical companies are rapidly internationalizing. Much research on internationalization exists, but none of them concentrate pharma companies. Methods: As a result, we examine the current state towards internationalization, as well as the feasibility of an international policy, with a sample of 30 global pharmaceutical companies. For the eight years, we had collected data on total sales and regional drug revenues, as well as marketing, general, and administrative expenses. The Microsoft office 365 and IBM SPSS statistical program for Windows, edition 26.0, was used to perform all statistical calculations in this report. Results: Camel are pharmaceutically important animal and has great contribution in economy. Many Pharmaceutical companies in their home regions switched to being multinational, their TS remained unchanged from 2010 to 2017 (Paired t-test, p = 0.352). However, companies that stayed focused on their home area increased their TS between 2010 and 2017 (Paired t-test, p = 0.053). Expansion of Asia-Pacific and Others have a inverse impact on the expansion of Total Sales (home-region-oriented: p < 0.05, r = -0.629; global: p = 0.161 r = -0.313), Although the development of North America, on the other hand, had a direct correlation with the growth of Total sales (home-region-oriented: p < 0.01, r = 0.818; global: p = 0.094, r = 0.408). Conclusion: This paper contributes to the awareness of the importance of camel's pharmaceutical products and international penetration strategies of pharmaceutical companies
Keywords: Pharmaceutical companies; Camel Products; International strategies; Globalization; Public awareness; General text